Ultra high dose rate Synchrotron Microbeam Radiation Therapy. Preclinical evidence in view of a clinical transfer. (October 2019) - Eling, Laura; Bouchet, Audrey; Nemoz, Christian; Djonov, Valentin; Balosso, Jacques; Laissue, Jean; Bräuer-Krisch, Elke; Adam, Jean Francois; Serduc, Raphael
Highlights: MRT is a form of synchrotron generated X-ray radiosurgery dedicated to brain tumours. Normal tissue tolerates high X-ray dose thanks through lattice of microbeams. MRT operates at very high dose rate (kGy·s −1 ) and triggers FLASH effect in vivo . Abstract: This paper reviews the current state of the art of an emerging form of radiosurgery dedicated to brain tumour treatment and which operates at very high dose rate (kGy·s −1 ). Microbeam Radiation Therapy uses synchrotron-generated X-rays which triggered normal tissue sparing partially mediated by FLASH effect.